FACTORS AND SOLUTIONS OF STUDENTS’ BULLYING BEHAVIOR - Damri, Damri; Engkizar, Engkizar; Syafril, Syafrimen; Asril, Zainal; K, Munawir; Rahawarin, Yunus; Tulum, La Mai; Asrida, Asrida; Amanda, Viola (STKIP Pesisir Selatan, 2020)
This study aims to analyzethe factors that cause bullying behavior among students and how to solve it. This study was employed a qualitative method with a case study approach. Sources of data were taken through in-depth interviews with twenty informants consisting of elementary school students, junior high schools, senior highschools, principals, teachers, school security guards, education observers and parents of students. All interview data were then analyzed thematically using NVivo 10 quality analysis software. Overall, the study found nine important themes. Four themes related to the factors causing bullying behavior, namely: i)entrenched beliefsamong students, ii) physical differences between the perpetrator and the victim, iii) discipline by seniors to juniors and iv) the condition of the victim's physical disability and weakness. Five themes related to solutions to tackling the problem of bullying, namely i) giving firm action to the perpetrator, ii) eliminating television shows related to violence, iii) equipping children with martial arts, iv) providing continuous education about the dangers of bullying, and v) instilling mutual respect in children